PERANCANGAN UI/UX START UP “PETS KITA” MENGGUNAKAN METODE USER CENTER DESIGN DAN ANALISIS GSTALT - Lubis, Hendarman -; Salman, Salman; Faujiyah, Firdhani (STMIK BINA PATRIA, 2026)
This study aims to design the User Interface (UI) and User Experience (UX) of the startup application “Pets Kita” by integrating the User-Centered Design (UCD) method and Gestalt principles. The rapid growth of the pet care industry in Indonesia highlights the need for a digital platform that provides integrated services, including pet healthcare, e-commerce, and community interaction. However, many existing applications suffer from poor usability and non-intuitive navigation. This research adopts a UCD approach consisting of four main stages: understanding the context of use, specifying user requirements, producing design solutions, and evaluating designs. Data were collected through observation and in-depth interviews with pet owners, followed by the development of user personas and user journey maps. The design process utilized Figma to create wireframes and high-fidelity prototypes, while Gestalt principles such as proximity, similarity, continuity, and closure were applied to enhance visual perception and usability. The evaluation phase employed usability testing and heuristic evaluation, resulting in an overall usability score of 83%, indicating that the proposed design meets user needs effectively. The findings demonstrate that integrating UCD and Gestalt principles can significantly improve usability, user satisfaction, and interaction efficiency. This study contributes to the development of user-friendly digital platforms in the pet care industry and provides a practical framework for UI/UX design in startup environments. Keywords: UI/UX, User-Centered Design, Gestalt, Startup, Pets Kita.